Talk on goods and services tax (GST) - Abg Affendie, Dayang Liyana (Universiti Teknologi MARA, Sarawak, 2015)
The objective of the talk was to enhance students’ understanding on the effects of GST and the country’s policies. It was also to fulfil part of the requirements of “Issue and Ethics in Finance” (FIN657) subject.